Racial disparities in BRCA testing and cancer risk management across a population-based sample of young breast cancer survivors - Cragun, Deborah (Cancer, 2017)
BACKGROUND: Breast cancer (BC) disparities may widen with genomic advances. We compared non-Hispanic white (NHW), Black, and Hispanic BC survivors for: 1) cancer risk management practices (CRM) among BRCA carriers; and 2) provider discussion and receipt of genetic testing. METHODS: A population-based sample of NHW, Black, and Hispanic women diagnosed with invasive BC ≤ age 50 in 2009–2012 were recruited through the state cancer registry. Using multiple logistic regression we compared CRM in BRCA carriers and association of demographic and clinical variables with provider discussion and receipt of testing. RESULTS: Of the 1622 participants, 36.1% (159/440) Blacks, 64.5% (579/897) NHW, 49.6% (58/117) Spanish-speaking Hispanics, and 69.0% (116/168) English-speaking Hispanics had BRCA testing, of whom 90 had a pathogenic BRCA mutation. Among BRCA carriers, RRM and RRSO rates were significantly lower among Blacks compared to Hispanics and NHW after controlling clinical and demographic variables (p=0.025 and 0.008, respectively). Compared to NHW, discussion of genetic testing with a provider was 16 times less likely among Blacks (p<0.0001) and nearly two times less likely among Spanish-speaking Hispanics (p=0.04) after controlling clinical and sociodemographic factors. CONCLUSIONS: Our results suggest lower rates of RRSO among Black compared to Hispanic and NHW BRCA carriers, which is concerning as benefits from genetic testing arise from CRM options. Furthermore, lower BRCA testing rates among Blacks may partially be due to lower likelihood of provider discussion. Future studies are needed to improve cancer risk identification and management practices across all populations to prevent the widening of disparities.